2017
DOI: 10.1111/etp.12226
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Entrepreneur–Investor Relationships: A Signaling Theory Approach

Abstract: This study adopts a gender perspective to analyze funding decisions made by an investment fund that invests equity stakes in new ventures. Prior research has indicated that there is gender skewness in risk capital investments resulting from a combination of demand‐ and supply‐side issues. We apply signaling theory to examine the interface between demand and supply to understand gender biases related to risk capital investments. In‐depth analyses of decision documents from four investment cases show that gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 72 publications
4
91
1
7
Order By: Relevance
“…Intellectual capital and family support push them to maximize their involvement in entrepreneurial activities. This result confirms and enriches the copious literature investigating the role of gender in the investor-entrepreneur relationship and its impact on entrepreneurial involvement (Alsos & Ljunggren, 2017;Malmström et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…Intellectual capital and family support push them to maximize their involvement in entrepreneurial activities. This result confirms and enriches the copious literature investigating the role of gender in the investor-entrepreneur relationship and its impact on entrepreneurial involvement (Alsos & Ljunggren, 2017;Malmström et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…Tinkler et al () concluded that the gender of the entrepreneur influenced evaluators most when the focus of evaluation is on the person, rather than on the venture. Finally, in a study of the perceived legitimacy of Norwegian small businesses, Alsos and Ljunggren () reported on how gender is embedded in the ways in which entrepreneurs signal and investors perceive firm quality. Their findings revealed that men were less likely to need signaling strategies than women.…”
Section: Review Of Literature On Access To Finance For Women Entreprementioning
confidence: 99%
“…However, research findings examining gender differences have shown contradicting results (Langowitz & Minniti, 2007;Wilson, Kickul, & Marlino, 2007); some investigators have found gender differences in entrepreneurial intention (Moore & Buttner, 1997;Zhao, Seibert, & Hills, 2005), but others have failed to confirm such differences (Calderon, Iacovone, & Juarez, 2017;Gupta, Turban, Wasti, & Skidar, 2009). Although most Western countries perform similarly in supporting female entrepreneurship, the US performs the best on indicators of good institutional support and strong overall entrepreneurial environment support for females (Alsos & Ljunggren, 2017;Dell Report, 2013). Currently, there are 8.6 million female-led businesses in the US, generating more than $1.3 trillion in revenues and employing nearly 8 million people (Casserly, 2013).…”
Section: Entrepreneurship In the Western Countriesmentioning
confidence: 99%